Primers for clinical detection of Paracoccidioides brasiliensis - San-Blas, G.; Nino-Vega, G.; Barreto, L.; Hebeler-Barbosa, F.; Bagagli, E.; de Briceno, R. O.; Mendes, R. P. (Amer Soc Microbiology, 2005)
From a 0.72-kb fragment universally generated in Paracoccidioides brasiliensis strains, primers were designed and tested on genomic DNA of this and other pathogenic fungi. They were specific and highly sensitive for P. brasiliensis DNA. Positive results were obtained when these were tested in clinical samples.